1998
DOI: 10.1073/pnas.95.13.7422
|View full text |Cite
|
Sign up to set email alerts
|

Role of p38 mitogen-activated protein kinase in HIV type 1 production in vitro

Abstract: The proinf lammatory cytokines interleukin (IL)-1 and tumor necrosis factor (TNF) promote HIV type 1 viral replication in vitro. In the present studies, HIV production was increased in the macrophagic U1 cell line expressing the HIV genome after exposure to IL-1␤, osmotic stress, or surface adhesion, suggesting a conf luence of signaling pathways for proinf lammatory cytokines and cell stressors. The p38 mitogen-activated protein kinase (MAPK) mediates both cytokine and stress responses; thus the role of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 28 publications
2
76
0
Order By: Relevance
“…An increasing amount of information has demonstrated that many viruses activate the p38 MAPK pathway to augment their efficient replication (51)(52)(53)(54)(55). To this end, although in our earlier study we have demonstrated that p38 MAPK activation is beneficial for ARV replication (31), its precise role in regulating ARV entry and replication remains elusive so far.…”
Section: Discussionmentioning
confidence: 91%
“…An increasing amount of information has demonstrated that many viruses activate the p38 MAPK pathway to augment their efficient replication (51)(52)(53)(54)(55). To this end, although in our earlier study we have demonstrated that p38 MAPK activation is beneficial for ARV replication (31), its precise role in regulating ARV entry and replication remains elusive so far.…”
Section: Discussionmentioning
confidence: 91%
“…However, R5 envelopes were more pronounced in their capacity to modulate the p38 MAPK cascade. The expression of p38 MAPK has been shown to positively correlate with HIV replication (37) and inhibitors of p38 kinase inhibit viral replication (37,38). Thus, the more pronounced activation of genes included in the p38 signaling cascade identifies one potential mechanism that favors R5 viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…IL-32 affects NF-B and p38MAPK in macrophages and T cells, the target cells of HIV-1. In addition, IL-32-induced IL-1␤, TNF-␣, IL-6, and chemokines (IL-8 and MIP-2) (2) are each relevant to the pathoimmunology of HIV-1 (14,15). We therefore investigated the role of this new cytokine in infection with HIV-1.…”
mentioning
confidence: 99%